2020
DOI: 10.1590/0034-7167-2018-0338
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding: what do women who participate in a prenatal group think?

Abstract: Objectives: to understand breastfeeding meanings and practices produced by women attending prenatal care at a Basic Health Unit in the Brazilian Northeast. Methods: a social research characterized as participant research. A Focal Group was conducted with nine pregnant women who had other children. For the analysis, Discursive Practices and Production of Meanings in Everyday Life perspectives were worked out. Results: prenatal care, mother-baby relationship, family, and pain/suffering categories were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
1
0
6
Order By: Relevance
“…A literatura aponta apoio insuficiente ou inadequado na atenção primária, durante o pré-natal e no pós-parto, no que se refere ao AM, assim como o preparo insuficiente da equipe para incentivar e apoiar as mulheres segundo suas necessidades individuais (23) . Esse apoio inadequado poderia se relacionar aos traumas mamilares Além disso, é recomendado que seja desenvolvida educação em serviço para os enfermeiros, de forma a promover a intervenção precoce no intuito de prevenir o trauma mamilar.…”
Section: Discussionunclassified
“…A literatura aponta apoio insuficiente ou inadequado na atenção primária, durante o pré-natal e no pós-parto, no que se refere ao AM, assim como o preparo insuficiente da equipe para incentivar e apoiar as mulheres segundo suas necessidades individuais (23) . Esse apoio inadequado poderia se relacionar aos traumas mamilares Além disso, é recomendado que seja desenvolvida educação em serviço para os enfermeiros, de forma a promover a intervenção precoce no intuito de prevenir o trauma mamilar.…”
Section: Discussionunclassified
“…Primary care units must take responsibility for providing updates to their professionals on different topics, procedures, care flows, and other aspects of the healthcare scenario through their managers. Studies (2,10) have indicated that better service performance is associated with, among other factors, better qualifications of professionals to develop practices that value the promotion, protection, and support of BF.…”
Section: Discussionmentioning
confidence: 99%
“…A dor no início do aleitamento é normal, mas a partir do momento em que surgem fissuras, bolhas e sangramento, esse momento passa a ser frustrante. Essas complicações são decorrentes da sucção, anatomia do mamilo, bebês com disfunções orais ou pela pega incorreta e, por isso, o acompanhamento da mãe durante e após a gestação, com orientações voltadas a singularidade de cada mulher é de extrema importância, pois diante das problemáticas e dos questionamentos existentes, os profissionais de saúde conseguem intervir e evitar o desmame precoce (21,25,(27)(28)(29) .…”
Section: Discussionunclassified